Gay Poz Sex: A Sexual Health Promotion Intervention for HIV-Positive Gay and Bisexual Men. Issue 4 (November 2016) - Hart, Trevor A.; Willis, Amy C.; Simpson, Scott H.; Julien, Rick E.; Hoe, David; Leahy, Bob; Maxwell, John; Adam, Barry D.
Abstract: Despite the widespread use of cognitive-behavioral therapy and motivational interviewing techniques among behavioral clinicians, most mental health clinicians do not know how to use these techniques for HIV prevention and sexual health promotion. Even less information is available to clinicians on how to work with HIV-positive gay and bisexual men who are at risk for transmitting HIV due to condomless anal sex. The purpose of the present paper is to assist behavioral therapists who are treating HIV-positive gay and bisexual men who engage in sexual behavior that may place them at risk for transmitting HIV or for other sexually transmitted infections. Gay Poz Sex is a form of small group counseling that uses the Information-Motivation-Behavioral Skills model (e.g., Fisher & Fisher, 2000) as the theoretical basis, and a combination of psychoeducation, motivational interviewing, and cognitive-behavioral skills such as stimulus control and role-play exercises. The treatment has the goal of promoting a positive sense of sexual well-being and reducing sexual behavior associated with the transmission of HIV, such as condomless anal sex. This paper illustrates, using three case examples, the application of empirically supported therapy techniques to reduce condomless anal sex for HIV-positive gay and bisexual men. Highlights: Gay Poz Sex (GPS) is a novel HIV prevention intervention for HIV-positive gay and bisexual men The information-motivation-behavioral skills model informs this group therapy GPS uses motivational interviewing, psychoeducation, and cognitive-behavioral skills We found reductions in participants' sexual risk behavior and loneliness